2013
DOI: 10.1128/aem.02831-13
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Salmonella and Listeria monocytogenes Contamination of Produce Fields

Abstract: cIdentification of management practices associated with preharvest pathogen contamination of produce fields is crucial to the development of effective Good Agricultural Practices (GAPs). A cross-sectional study was conducted to (i) determine management practices associated with a Salmonella-or Listeria monocytogenes-positive field and (ii) quantify the frequency of these pathogens in irrigation and nonirrigation water sources. Over 5 weeks, 21 produce farms in New York State were visited. Fieldlevel management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
122
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(141 citation statements)
references
References 61 publications
5
122
3
Order By: Relevance
“…2). Previous work also has shown that generic E. coli (18), E. coli O157:H7 (27), Salmonella (28), and Listeria (29,30) are positively associated with livestock density or proximity to livestock. Similarly, studies that have aggregated reported EHEC illnesses to county or district levels have generally observed higher EHEC infection rates in counties with higher cattle densities, although this approach infers rather than directly links cases and exposures (19,20).…”
Section: Discussionmentioning
confidence: 97%
“…2). Previous work also has shown that generic E. coli (18), E. coli O157:H7 (27), Salmonella (28), and Listeria (29,30) are positively associated with livestock density or proximity to livestock. Similarly, studies that have aggregated reported EHEC illnesses to county or district levels have generally observed higher EHEC infection rates in counties with higher cattle densities, although this approach infers rather than directly links cases and exposures (19,20).…”
Section: Discussionmentioning
confidence: 97%
“…An epidemiological study by Strawn et al (22) reported that irrigation of field more than 3 days prior to sample collection reduced the odds of L. monocytogenes isolation from soil and drag swab samples in a produce field. Similarly, our previous study (6) showed that spinach irrigated more than 5 days prior to harvest had nearly 76% lower odds of generic E. coli isolation compared to spinach irrigated 5 days or less prior (OR ϭ 0.24).…”
Section: Discussionmentioning
confidence: 99%
“…Wildlife are well known as carriers of pathogens causing foodborne illnesses. Strawn et al (22) reported that observation of wildlife within 3 days prior to sampling increases odds of L. monocytogenes isolation from soil and drag swab samples in a produce field. Other studies (15,22) have also suggested wildlife are an important source of pathogen transmission to produce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations